Examination of IL-1β level as an inflammasome marker in Alzheimer's disease - (:unkn) unknown (AVES, 2019)
Objective: Interleukin (IL)-1β is believed to be responsible for the neurotoxicity of amyloid plaques in Alzheimer’s disease (AD). In the present study, serum levels of IL-1β, and correlations with clinical features and neuropsychiatric test results were examined. Methods: Thirty-eight patients with AD and 38 healthy control patients were included in the study. Serum IL-1β levels in patients with AD and control were analyzed using enzyme-linked immunosorbent assay method. The Mini-Mental Test Score (MMSE) and Geriatric Depression Scale (GDS) were administered to both the patient and control groups. Furthermore, the clinical dementia rating, detailed neuropsychological test battery, and neuropsychiatric inventory were administered to the AD group. It was determined that the serum IL-1β measurements of the patient and control groups were not statistically different, and IL-1β measurements in the patient group were not correlated with the MMSE and GDS. Results: The relationship of IL-1β measurements in the patient group with other clinical data was not significant. Among the patients' neuropsychological tests, a moderately, significant negative correlation was found only between the clock drawing test and visual learning score and serum IL-1β levels. Conclusion: Our study is in agreement with other studies in which no significant difference was found between patients with AD and healthy controls in terms of serum IL-1β levels, but the moderately negative correlation obtained with the clock drawing test and visual learning score indicates a weak relation. This result may indicate that stronger relations will be determined in large-scale studies involving larger numbers of patients. © 2019, AVES. All rights reserved.
Keywords: Alzheimer's disease; Cytokine; Dementia; Enzyme linked immunosorbent assay; Interleukin-1β